The Impact of Monetary Policy Transmission on Economic Growth in Sumatra Island - Dina Octaviani; Muh. Rudi Nugroho (Universitas Ibn Khladun Bogor, 2026)
This study aims to analyze the effect of monetary policy transmission channels on economic growth across all provinces in Sumatra Island from 2015 to 2025. The variables examined include the BI Rate (X1), Inflation (X2), Money Supply (X3), and Exchange Rate (X4), with Economic Growth (Y) as the dependent variable. Utilizing quarterly secondary panel data sourced from Bank Indonesia and the Central Bureau of Statistics (BPS), this study employs a Panel Data Regression approach. Based on the Chow and Hausman tests, the Fixed Effect Model (FEM) was selected as the best estimation model. The results of the partial analysis (t-test) show that the BI Rate has a significant positive effect on economic growth, while the Money Supply has a significant negative effect. Conversely, Inflation and the Exchange Rate do not show any significant impact on economic growth in Sumatra. Simultaneously (F-test), all independent variables significantly influence economic growth. The Adjusted R-squared value indicates that the monetary variables simultaneously explain 14.74% of the variation in economic growth, while the remaining 85.26% is explained by other factors outside the model.